INVESTIGATED LANGUAGE PROFILING AS AN IDENTIFICATION TOOL FOR PETITIONED OFFENSE OF FRAUD AND DEFAMATION - Tsurayya Yusra Zahirah Zahra; Sailal Arimi (JURNAL PENDIDIKAN, HUMANIORA, LINGUISTIK DAN SOSIAL (JAGADDHITA), 2026)
This study analyzes the function of language in the legal realm, using the Linguistic Speaker Profiling to identify language violations committed by MZ suspects with petitioned offenses of fraud and defamation. Based on the background and motive of the suspect recorded in the case evidence (CE). This study uses a qualitative method with a Forensic Linguistic approach. The theory of the basic principles of Forensic Linguistics described by Gibbons and Warami was used as the basis of the research analysis. The results obtained are that the Linguistic Speaker Profiling Medina Zein (MZ) was studied with meaning aspects. The results of the meaning aspect on the Suspect's Linguistic Profile show that there are five identifications of potential language crimes, ranging from lies, insults, and fraud to defamation. Meanwhile, the phonetic aspect will not be discussed further in this study, this is because the focus of the researchers is to show the form, function, and benefits of using speaker profiling by only analyzing the meaning aspect. This research is expected to add value to the legality of speaker profiling as a legal method of forensic linguistic analysis in the process of investigating legal cases, especially in Indonesia.